Preparation method and application of sodium-ion double-layer solid electrolyte of sodium-ion battery

By using a combination technology of organic polymers and inorganic powders in sodium-ion batteries, and using the spin coating method to form a double-layer solid electrolyte, the problems of uneven dispersion and loose interface integration are solved, and the electrochemical performance of the battery is significantly improved.

CN119340456APending Publication Date: 2025-01-21ZHEJIANG HUAYU NADIAN NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411506083.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing sodium ion bilayer solid electrolyte preparation methods have problems such as uneven dispersion and inability to closely combine the interface, resulting in large battery impedance and affecting electrochemical performance.

Method used

The organic polymer and sodium salt are dissolved in the organic solvent and then poured to form an organic solid electrolyte; then the inorganic powder and sodium salt are dissolved in the organic solvent, and an inorganic layer is formed on the organic solid electrolyte through spin coating technology, and then left to dry to obtain Sodium ion double layer solid electrolyte.

Benefits of technology

The sodium ion double-layer solid electrolyte prepared by this method can improve ionic conductivity, generate a stable SEI interface, improve electrochemical performance, and significantly improve the discharge specific capacity and capacity retention rate of button batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340456A_ABST
    Figure CN119340456A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a sodium ion double-layer solid electrolyte, and belongs to the technical field of solid sodium batteries. The specific preparation method comprises the following steps: dissolving an organic polymer and a sodium salt in an organic solvent to obtain slurry, pouring the slurry, and standing and drying after pouring to obtain the organic solid electrolyte, and dissolving inorganic powder and sodium salt in an organic solvent to obtain inorganic slurry, rotatably coating the organic solid electrolyte with the inorganic slurry, and standing and drying to obtain the sodium ion double-layer solid electrolyte. The button cell prepared from the sodium ion double-layer solid electrolyte obtained by the preparation method has good electrochemical performance and relatively high specific discharge capacity and capacity retention ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state sodium batteries, and in particular relates to a preparation method and application of a sodium ion double-layer solid electrolyte for a sodium ion battery. Background Art

[0002] Sodium-ion batteries have great potential for large-scale energy storage due to their low cost and compatibility with other batteries. Similar to lithium-ion batteries that use flammable liquid electrolytes, sodium-ion batteries also have safety issues. Organic polymer solid electrolytes are considered to be a good solution to this problem. They have good contact with sodium metal anodes and are more compatible with sodium metal anodes, but their low ionic conductivity at room temperature is not conducive to the transmission of sodium ions, which limits their widespread application. Inorganic solid electrolytes, such as oxide solid electrolytes, have good thermal stability and ionic conductivity, and can promote the rapid movement of sodium ions. However, due to the problem of solid-solid contact, the electrolyte has poor compatibility with the anode interface and high interface resistance, which easily leads to the growth of sodium dendrites and electrolyte failure. Sodium ion double-layer solid electrolytes, that is, the combination of inorganic solid electrolytes and organic polymer solid electrolytes, can effectively solve the shortcomings of both. It can not only improve ionic conductivity, but also generate a stable SEI interface, and has been widely studied.

[0003] At present, the preparation method of sodium ion double-layer solid electrolyte is limited to simple methods such as coating and casting. For example, the coating method used in patent CN108767311B is to flow the slurry out of the slit of the coating die head and then flow downward along the slope surface, and then form a liquid bridge at the gap between the coating roller and the slope coating die head, and be taken away by the running carrier to form one or more layers of coating, drying, and peeling the carrier to obtain a composite electrolyte membrane of a solid-state battery. Patent CN114243100A uses a casting method to cast the positive electrode side electrolyte onto the positive electrode. Although the above-mentioned coating and casting methods are simple to operate, they have great defects. First, the solid electrolyte prepared by this method is too different, and the process conditions of each casting and coating are different, and a fixed solid electrolyte cannot be formed. Secondly, the casting and coating process slurry is unevenly dispersed, cracks and other phenomena will occur, and the interface between the solid electrolytes cannot be tightly combined, which easily leads to an increase in battery impedance and greatly affects the electrochemical performance of the battery. Therefore, the prior art is in urgent need of a method for preparing a sodium ion double-layer solid electrolyte. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of a sodium ion double-layer solid electrolyte for a sodium ion battery, so as to solve the problems of uneven dispersion, inability to tightly bond the interface, and high battery impedance during the preparation of the solid electrolyte.

[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions: The invention discloses a sodium ion double-layer solid electrolyte, comprising: an organic polymer, a sodium salt and an inorganic powder; the organic polymer comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, cross-linked polyetherimide and polyhexylene adipate. The use of cross-linked polyetherimide and polyhexylene adipate is conducive to the interaction between sodium ions and polymer matrix, increases the migration of sodium ions, and is more compatible with electrodes to form a stable interface, thereby improving electrochemical performance.

[0006] Preferably, the sodium salt is at least one of sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate and sodium perchlorate.

[0007] Preferably, the inorganic powder is Na3Zr2Si2PO 12 、Li7La3Zr2O 12 and Li 6.4 LqCy 1.4 Ta 0.6 O 12 At least one of .

[0008] Preferably, in the above sodium ion double-layer solid electrolyte, the mass ratio of the amount of organic polymer used to the amount of sodium salt used is 1:0.1-1.68, and the mass ratio of the amount of inorganic powder used to the amount of sodium salt used is 1:0.382-2.5.

[0009] The present invention discloses a method for preparing a sodium ion double-layer solid electrolyte, comprising: S1: dissolving an organic polymer and a sodium salt in an organic solvent to obtain a slurry, casting the slurry, and standing the slurry to dry to obtain an organic solid electrolyte; S2: Preparation of a sodium ion double-layer solid electrolyte, dissolving an inorganic powder and a sodium salt in an organic solvent to obtain an inorganic slurry, then rotating the inorganic slurry on the organic solid electrolyte prepared in S1, and letting it stand and dry to obtain a sodium ion double-layer solid electrolyte.

[0010] Preferably, the organic polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, cross-linked polyetherimide and polyhexamethylene adipate.

[0011] Preferably, the sodium salt is at least one of sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate and sodium perchlorate.

[0012] Preferably, the inorganic powder is Na3Zr2Si2PO 12 、Li7La3Zr2O 12 and Li 6.4 LqCy 1.4 Ta 0.6 O12 At least one of .

[0013] Preferably, the organic solvent is at least one of acetonitrile, N-methylpyrrolidone and acetone.

[0014] Preferably, the mass ratio of the amount of the organic polymer used in S1 to the amount of the sodium salt used is 1:0.08-0.8.

[0015] Preferably, the amount of the organic polymer in the organic reagent in S1 is 0.05-0.15 g / ml.

[0016] Preferably, the mass ratio of the amount of inorganic powder used in S2 to the amount of sodium salt used is 1:0.2-0.5.

[0017] Preferably, the amount of the inorganic powder in the organic reagent in S2 is 0.07-0.15 g / ml.

[0018] Preferably, in S1, the standing temperature is 23-27° C., and the standing time is 6-15 h; the drying temperature is 45-65° C., and the drying time is 4-10 h.

[0019] Preferably, in S2, the standing temperature is 23-27° C., and the standing time is 10-15 h; the drying temperature is 40-55° C., and the drying time is 4-10 h.

[0020] The invention discloses a battery, comprising the sodium ion double-layer solid electrolyte or the sodium ion double-layer solid electrolyte prepared by the above method or the sodium ion double-layer solid electrolyte prepared by the above method.

[0021] The present invention discloses a method for preparing a sodium ion double-layer solid electrolyte, comprising: S1: Preparation of an organic solid electrolyte, dissolving an organic polymer and a sodium salt in an organic solvent to obtain a slurry, casting the slurry, and standing and drying after casting to obtain an organic solid electrolyte; S2: Preparation of a sodium ion double-layer solid electrolyte, dissolving an inorganic powder and a sodium salt in an organic solvent to obtain an inorganic slurry, then rotating the inorganic slurry on the organic solid electrolyte prepared in S1, and letting it stand and dry to obtain a sodium ion double-layer solid electrolyte.

[0022] Preferably, in the above technical solution, the organic polymer includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, cross-linked polyetherimide and poly(hexamethylene adipate).

[0023] Preferably, in the above technical solution, the sodium salt is at least one of sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate and sodium perchlorate.

[0024] Preferably, in the above technical solution, the inorganic powder is Na3Zr2Si2PO 12 、Li7La3Zr2O 12 and Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 At least one of .

[0025] Preferably, in the above technical solution, the organic solvent is at least one of acetonitrile, N-methylpyrrolidone and acetone.

[0026] Preferably, in the above technical solution, the mass ratio of the amount of organic polymer used in S1 to the amount of sodium salt used is 1:0.08-0.8.

[0027] Preferably, in the above technical solution, the amount of the organic polymer in S1 in the organic reagent is 0.05-0.15 g / ml.

[0028] Preferably, in the above technical solution, the mass ratio of the amount of inorganic powder used in S2 to the amount of sodium salt used is 1:0.2-0.5.

[0029] Preferably, in the above technical solution, the amount of the inorganic powder in S2 in the organic reagent is 0.07-0.15 g / ml.

[0030] Preferably, in the above technical solution, the mass ratio of the amount of sodium salt used in the organic solid electrolyte to the amount of sodium salt used in the inorganic slurry is 1:0.2-1.1.

[0031] Preferably, in the above technical solution, the standing temperature in S1 is 23-27°C, and the standing time is 6-15h; the drying temperature is 45-65°C, and the drying time is 4-10h.

[0032] Preferably, in the above technical solution, the standing temperature in S2 is 23-27°C, and the standing time is 10-15h; the drying temperature is 40-55°C, and the drying time is 4-10h.

[0033] Preferably, in the above technical solution, the rotation speed of the rotary coating in S2 is 150-250 rpm.

[0034] The present invention discloses a method for preparing a cross-linked polyetherimide, which is specifically: First, 4,4'-diaminodiphenyl ether and BPA-type diether dianhydride are added to DMAc to obtain a mixture and a first reaction is carried out. Then, 4-phenylethynylphthalic anhydride and DMAc are added to the mixture to continue a second reaction. After the reaction is completed, triethylamine and acetic anhydride are added to carry out a third reaction. Finally, the cross-linked polyetherimide is obtained after washing and vacuum drying.

[0035] Preferably, the mass ratio of the amount of 4,4'-diaminodiphenyl ether used to the amount of BPA-type diether dianhydride used is 1:2-3.

[0036] Preferably, the amount of 4,4'-diaminodiphenyl ether added to DMAc is 0.04-0.08 g / ml.

[0037] Preferably, the mass ratio of the amount of 4-phenylethynylphthalic anhydride used to the amount of BPA-type diether dianhydride used is 1:0.07-0.11.

[0038] Preferably, the volume ratio of the amount of DMAc added to the mixture to the amount of DMAc in the mixture is 1:0.03-0.06.

[0039] Preferably, the mass ratio of the amount of triethylamine used to the amount of BPA-type diether dianhydride used is 1:0.5-0.8.

[0040] Preferably, the mass ratio of the amount of acetic anhydride used to the amount of BPA-type diether dianhydride used is 1:0.5-0.8.

[0041] Preferably, the reaction temperature of the first reaction is 23-27° C., and the reaction time is 8-15 h.

[0042] Preferably, the reaction temperature of the secondary reaction is 23-27° C., and the reaction time is 4-8 h.

[0043] Preferably, the reaction temperature of the third reaction is 23-27° C., and the reaction time is 2-5 h.

[0044] Preferably, the reagent used for washing is ethanol, and the number of washing times is 4-7 times.

[0045] Preferably, the vacuum drying temperature is 75-85° C., and the vacuum drying time is 5-15 h.

[0046] Preferably, the entire preparation process is under argon conditions.

[0047] More preferably, in the preparation of the sodium ion double-layer solid electrolyte, on the basis of using an organic polymer, 2-hydroxyglutarate diethyl ester can also be added. The organic polymer is polyvinylidene fluoride, cross-linked polyetherimide and polyhexanediol adipate. The use of 2-hydroxyglutarate diethyl ester can affect the structure and arrangement of the polymer chain, improve the ionic conductivity and electrolyte stability, and thus improve the electrochemical performance.

[0048] Preferably, the mass ratio of the amount of diethyl 2-hydroxyglutarate to the amount of polyvinylidene fluoride is 1:9-11.

[0049] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a preparation method and application of a sodium ion double-layer solid electrolyte, wherein an organic polymer and a sodium salt are dissolved in an organic solvent to obtain a slurry, the slurry is cast, and after casting, it is allowed to stand and dry to obtain an organic solid electrolyte; then an inorganic powder and a sodium salt are dissolved in an organic solvent to obtain an inorganic slurry, the inorganic slurry is rotatably applied on the organic solid electrolyte, and after standing and drying, a sodium ion double-layer solid electrolyte is obtained. The button battery made of the sodium ion double-layer solid electrolyte obtained by this preparation method has good electrochemical properties, and has a high discharge specific capacity and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0051] Figure 1 It is a structural schematic diagram of a rotary coating device; Figure 2 This is a SEM image of the sodium ion double-layer solid electrolyte prepared in Example 1; Figure 3 This is a SEM image of the sodium ion double-layer solid electrolyte prepared in Comparative Example 3; Figure 4 This is a SEM cross-sectional view of the sodium ion double-layer solid electrolyte prepared in Example 1; Figure 5 It is the charge and discharge curve of button battery; Figure 6 This is the cycle performance diagram of the button battery. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.

[0054] Embodiment 1: Preparation of organic solid electrolyte: polyvinylidene fluoride and sodium bis(trifluoromethylsulfonyl imide) were dissolved in acetone to obtain slurry, and then the slurry was poured into a polytetrafluoroethylene mold, left to stand at 25°C for 12 hours, and then dried at 50°C for 6 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride used to the amount of sodium bis(trifluoromethylsulfonyl imide) used was 1:0.5, and the amount of polyvinylidene fluoride in acetone was 0.083 g / ml.

[0055] Preparation of sodium ion double-layer solid electrolyte: Na3Zr2Si2PO 12 The powder and sodium bis(trifluoromethylsulfonyl imide) were dissolved in acetone to obtain an inorganic slurry. Then, the organic solid electrolyte was fixed on a rotary coating device, and then the inorganic slurry was dripped on the center of the rotary coating device rotating at a speed of 200 rpm. After the dripping was completed, it was left to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion double-layer solid electrolyte. Among them, Na3Zr2Si2PO 12 The mass ratio of the powder used and the sodium bis(trifluoromethylsulfonyl)imide used is 1:0.25, Na3Zr2Si2PO 12 The amount of powder in acetone is 0.1 g / ml, and the mass ratio of the amount of sodium bis(trifluoromethylsulfonyl imide) used in the organic solid electrolyte to the amount of sodium bis(trifluoromethylsulfonyl imide) used in the inorganic slurry is 1:0.25. Figure 1 shown.

[0056] Embodiment 2: Preparation of organic solid electrolyte: polyvinylidene fluoride-hexafluoropropylene and sodium hexafluorophosphate are dissolved in N-methylpyrrolidone to obtain slurry, and then the slurry is poured into a polytetrafluoroethylene mold, left to stand at 25°C for 10 hours, and then dried at 55°C for 5 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride-hexafluoropropylene used to the amount of sodium hexafluorophosphate used is 1:0.2, and the amount of polyvinylidene fluoride-hexafluoropropylene in N-methylpyrrolidone is 0.1g / ml.

[0057] Preparation of sodium ion double-layer solid electrolyte: Li7La3Zr2O 12 The powder and sodium hexafluorophosphate were dissolved in N-methylpyrrolidone to obtain an inorganic slurry. Then, the organic solid electrolyte was fixed on a rotary coating device, and then the inorganic slurry was dripped on the center of the rotary coating device rotating at a speed of 200 rpm. After the dripping was completed, it was left to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion double-layer solid electrolyte. Among them, Li7La3Zr2O 12 The mass ratio of the powder used to the sodium hexafluorophosphate used is 1:0.5, Li7La3Zr2O12 The amount of the powder in N-methylpyrrolidone is 0.067 g / ml, and the mass ratio of the amount of sodium hexafluorophosphate used in the organic solid electrolyte to the amount of sodium hexafluorophosphate used in the inorganic slurry is 1:1.

[0058] Embodiment 3: Preparation of organic solid electrolyte: Polyethylene oxide and sodium perchlorate are dissolved in acetonitrile to obtain slurry, and then the slurry is poured into a polytetrafluoroethylene mold, left to stand at 25°C for 8 hours, and then dried at 60°C for 4 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyethylene oxide used to the amount of sodium perchlorate used is 1:0.25, and the amount of polyethylene oxide in acetonitrile is 0.1 g / ml.

[0059] Preparation of sodium ion double-layer solid electrolyte: Li 6.4 LqCy 1.4 Ta 0.6 O 12 The powder and sodium perchlorate were dissolved in acetonitrile to obtain an inorganic slurry. Then, the organic solid electrolyte was fixed on a rotary coating device, and then the inorganic slurry was dripped on the center of the rotary coating device rotating at a speed of 150 rpm. After the dripping was completed, it was left to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion double-layer solid electrolyte. Among them, Li 6.4 LqCy 1.4 Ta 0.6 O 12 The mass ratio of the amount of powder used to the amount of sodium hexafluorophosphate used is 1:0.5, Li 6.4 LqCy 1.4 Ta 0.6 O 12 The amount of the powder in acetonitrile is 0.05 g / ml, and the mass ratio of the amount of sodium perchlorate used in the organic solid electrolyte to the amount of sodium perchlorate used in the inorganic slurry is 1:0.5.

[0060] Embodiment 4: Preparation of organic solid electrolyte: polyvinylidene fluoride-hexafluoropropylene and sodium bis(trifluoromethylsulfonyl imide) were dissolved in acetonitrile to obtain slurry, and then the slurry was poured into a polytetrafluoroethylene mold, left to stand at 25°C for 8 hours, and then dried at 50°C for 4 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride-hexafluoropropylene to the amount of sodium bis(trifluoromethylsulfonyl imide) was 1:0.33, and the amount of polyvinylidene fluoride-hexafluoropropylene in acetonitrile was 0.075 g / ml.

[0061] Preparation of sodium ion double-layer solid electrolyte: Na3Zr2Si2PO 12The powder and sodium bis(trifluoromethylsulfonyl imide) were dissolved in acetonitrile to obtain an inorganic slurry. Then, the organic solid electrolyte was fixed on a rotary coating device, and then the inorganic slurry was dripped on the center of the rotary coating device rotating at a speed of 150 rpm. After the dripping was completed, it was left to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion double-layer solid electrolyte. Among them, Na3Zr2Si2PO 12 The mass ratio of the powder used and the sodium bis(trifluoromethylsulfonyl)imide used is 1:0.5, Na3Zr2Si2PO 12 The amount of the powder in acetonitrile is 0.05 g / ml, and the mass ratio of the amount of sodium bis(trifluoromethylsulfonyl imide) used in the organic solid electrolyte to the amount of sodium bis(trifluoromethylsulfonyl imide) used in the inorganic slurry is 1:0.5.

[0062] Embodiment 5: Preparation of cross-linked polyetherimide: 4,4'-diaminodiphenyl ether and BPA-type diether dianhydride were added to DMAc to obtain a mixture, followed by reaction at 25°C for 10 hours, and then 4-phenylethynylphthalic anhydride and DMAc were added to the mixture, and the mixture was reacted at 25°C for another 5 hours. After the reaction, triethylamine and acetic anhydride were added, and the mixture was reacted at 25°C for 3 hours. Finally, the mixture was washed with ethanol for 5 times and vacuum dried at 80°C for 8 hours to obtain cross-linked polyetherimide. The mass ratio of 4,4'-diaminodiphenyl ether to BPA type diether dianhydride is 1:2.36, the amount of 4,4'-diaminodiphenyl ether added to DMAc is 0.066 g / ml, the mass ratio of 4-phenylethynylphthalic anhydride to BPA type diether dianhydride is 1:0.095, the volume ratio of DMAc added to the mixture to the amount of DMAc in the mixture is 1:0.045, the mass ratio of triethylamine to BPA type diether dianhydride is 1:0.642, the mass ratio of acetic anhydride to BPA type diether dianhydride is 1:0.647, and the entire preparation process is carried out under argon conditions.

[0063] Preparation of organic solid electrolyte: polyvinylidene fluoride, cross-linked polyetherimide, poly(hexanediol adipate) and sodium bis(trifluoromethylsulfonyl imide) are dissolved in acetone to obtain a slurry, and then the slurry is poured into a polytetrafluoroethylene mold, left to stand at 25°C for 12 hours, and then dried at 50°C for 6 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.5, the mass ratio of the amount of cross-linked polyetherimide to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.1, the mass ratio of the amount of poly(hexanediol adipate) to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.1, and the amount of polyvinylidene fluoride in acetone is 0.083 g / ml.

[0064] The preparation of the sodium ion double-layer solid electrolyte is the same as in Example 1.

[0065] Embodiment 6: The preparation of cross-linked polyetherimide is the same as in Example 5.

[0066] Preparation of organic solid electrolyte: polyvinylidene fluoride, cross-linked polyetherimide, poly(hexanediol adipate), sodium bis(trifluoromethylsulfonyl imide) and diethyl 2-hydroxyglutarate are dissolved in acetone to obtain slurry, and then the slurry is poured into a polytetrafluoroethylene mold, left to stand at 25°C for 12 hours, and then dried at 50°C for 6 hours to obtain an organic solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.5, the mass ratio of the amount of cross-linked polyetherimide to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.1, the mass ratio of the amount of poly(hexanediol adipate) to the amount of sodium bis(trifluoromethylsulfonyl imide) is 1:0.1, the mass ratio of the amount of diethyl 2-hydroxyglutarate to the amount of polyvinylidene fluoride is 1:10, and the amount of polyvinylidene fluoride in acetone is 0.083 g / ml.

[0067] The preparation of the sodium ion double-layer solid electrolyte is the same as in Example 1.

[0068] Embodiment 7: The preparation of cross-linked polyetherimide is the same as in Example 5.

[0069] The preparation of diethyl 2-hydroxyglutarate is the same as in Example 6.

[0070] Preparation of organic solid electrolyte: The preparation of the organic solid electrolyte in this embodiment is different from that in Example 6, except that the mass ratio of the amount of diethyl 2-hydroxyglutarate used to the amount of polyvinylidene fluoride used is 1:15, and the other conditions and parameters are the same as in Example 6.

[0071] The preparation of the sodium ion double-layer solid electrolyte is the same as in Example 1.

[0072] Comparative Example 1: Preparation of sodium ion single-layer solid electrolyte: polyvinylidene fluoride and sodium bis(trifluoromethylsulfonyl imide) were dissolved in acetone to obtain polyvinylidene fluoride slurry, and then the polyvinylidene fluoride slurry was poured into a polytetrafluoroethylene mold, left to stand at 25°C for 12 hours, and then dried at 50°C for 6 hours to obtain a sodium ion single-layer solid electrolyte. The mass ratio of the amount of polyvinylidene fluoride used to the amount of sodium bis(trifluoromethylsulfonyl imide) used was 1:0.5, and the amount of polyvinylidene fluoride in acetone was 0.083 g / ml.

[0073] Comparative Example 2: Preparation of sodium ion single-layer solid electrolyte: Na3Zr2Si2PO 12 The powder and sodium bis(trifluoromethylsulfonyl)imide were dissolved in acetone to obtain an inorganic slurry. The inorganic slurry was then poured into a polytetrafluoroethylene mold, left to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion single-layer solid electrolyte. 12 The mass ratio of the powder used and the sodium bis(trifluoromethylsulfonyl)imide used is 1:0.25, Na3Zr2Si2PO 12 The amount of powder in acetone was 0.1 g / ml.

[0074] Comparative Example 3: The preparation of the organic solid electrolyte is the same as in Example 1.

[0075] Preparation of sodium ion double-layer solid electrolyte: Na3Zr2Si2PO 12 The powder and sodium bis(trifluoromethylsulfonyl)imide were dissolved in acetone to obtain an inorganic slurry. The inorganic slurry was then poured into the organic solid electrolyte, and after pouring, it was allowed to stand at 25°C for 12 hours, and then dried at 45°C for 6 hours to obtain a sodium ion double-layer solid electrolyte. 12 The mass ratio of the powder used and the sodium bis(trifluoromethylsulfonyl)imide used is 1:0.25, Na3Zr2Si2PO 12 The amount of the powder in acetone is 0.1 g / ml, and the mass ratio of the amount of sodium bis(trifluoromethylsulfonyl imide) used in the organic solid electrolyte to the amount of sodium bis(trifluoromethylsulfonyl imide) used in the inorganic slurry is 1:0.25.

[0076] Comparative Example 4: Preparation of organic solid electrolyte: The preparation of the organic solid electrolyte in this embodiment is different from that in Example 5, except that no cross-linked polyetherimide is used, and other conditions and parameters are the same as in Example 5.

[0077] The preparation of the sodium ion double-layer solid electrolyte is the same as in Example 1.

[0078] Comparative Example 5: Preparation of organic solid electrolyte: The preparation of the organic solid electrolyte in this embodiment is different from that in Example 5, except that poly(hexamethylene adipate) is not used, and other conditions and parameters are the same as in Example 5.

[0079] The preparation of the sodium ion double-layer solid electrolyte is the same as in Example 1.

[0080] Experimental Example 1: The sodium ion double-layer solid electrolyte prepared in Example 1 was analyzed by scanning electron microscopy. The SEM morphology results are as follows Figure 2As shown, the inorganic slurry evenly covers the surface of the organic solid electrolyte without any cracks or particle accumulation.

[0081] Experimental Example 2: The sodium ion double-layer solid electrolyte prepared in Comparative Example 3 was analyzed by scanning electron microscopy. The SEM morphology results are as follows Figure 3 As shown, the sodium ion double-layer solid electrolyte has accumulation phenomenon and the uneven dispersion leads to cracks.

[0082] Experimental Example 3: The sodium ion double-layer solid electrolyte prepared in Example 1 was analyzed by scanning electron microscopy. The SEM cross-sectional view is as follows Figure 4 As shown, the inorganic slurry is closely connected with the organic solid electrolyte and can form a continuous sodium ion double-layer solid electrolyte.

[0083] Experimental Example 4: The solid electrolytes prepared in Examples 1-7 and Comparative Examples 1-5 were mixed with sodium nickel iron manganese oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 (NFM111) positive electrode sheet and sodium metal negative electrode were assembled into button cells in an argon atmosphere in sequence, and the discharge specific capacity of the button cells was measured. The solid electrolyte included the sodium ion double-layer solid electrolyte prepared in Examples 1-7 and Comparative Examples 3-5 and the sodium ion single-layer solid electrolyte prepared in Comparative Example 1-2.

[0084] Table 1 Discharge capacity results of button batteries

[0085] The results are shown in Table 1. The discharge specific capacity of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 1 of the present invention is higher than the discharge specific capacity of the button battery made of the sodium ion single-layer solid electrolyte prepared in Comparative Examples 1-2, indicating that the sodium ion double-layer solid electrolyte can fully transport sodium ions, thereby improving the discharge specific capacity; the discharge specific capacity of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 1 of the present invention is higher than that of Comparative Example 3, indicating that the preparation of the sodium ion double-layer solid electrolyte by a rotary coating device is better than that by direct casting; the discharge specific capacity of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 5 of the present invention is higher than that of Example 1, indicating that the cross-linked The use of cross-linked polyetherimide and poly(hexylene adipate) can improve the discharge specific capacity of the button battery made of sodium ion double-layer solid electrolyte; compared with Example 6, Example 5 of the present invention shows that on the basis of using polyvinylidene fluoride, cross-linked polyetherimide and poly(hexylene adipate), 2-hydroxyglutarate diethyl ester can be added to further improve the discharge specific capacity of the button battery made of sodium ion double-layer solid electrolyte; compared with Comparative Examples 4-5, Example 5 of the present invention shows that cross-linked polyetherimide and poly(hexylene adipate) need to be used together, and the use of any one of them alone has no obvious effect on improving the discharge specific capacity of the button battery made of sodium ion double-layer solid electrolyte.

[0086] Experimental Example 5: The solid electrolytes prepared in Examples 1-7 and Comparative Examples 1-5 were mixed with sodium nickel iron manganese oxide NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2 (NFM111) positive electrode sheet and sodium metal negative electrode are sequentially assembled into button cells in an argon atmosphere. The 200 cycle capacity retention rate of the button cells is measured. The solid electrolyte includes the sodium ion double-layer solid electrolyte prepared in Examples 1-7 and Comparative Examples 3-5 and the sodium ion single-layer solid electrolyte prepared in Comparative Example 1-2.

[0087] Table 2 Capacity retention results of button batteries

[0088] The results are shown in Table 2. The capacity retention rate of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 1 of the present invention is higher than that of the button battery made of the sodium ion single-layer solid electrolyte prepared in Comparative Examples 1-2, indicating that the sodium ion double-layer solid electrolyte can take into account the interface compatibility problem, thereby improving the capacity retention rate; the capacity retention rate of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 1 of the present invention is higher than that of Comparative Example 3, indicating that the sodium ion double-layer solid electrolyte prepared by a rotary coating device is better than that prepared by direct casting; the capacity retention rate of the button battery made of the sodium ion double-layer solid electrolyte prepared in Example 5 of the present invention is higher than that of Example 1, indicating that the cross The use of cross-linked polyetherimide and poly(hexylene adipate) can improve the capacity retention rate of button batteries made of sodium ion double-layer solid electrolytes; compared with Example 6, Example 5 of the present invention shows that on the basis of using polyvinylidene fluoride, cross-linked polyetherimide and poly(hexylene adipate), 2-hydroxyglutarate diethyl ester can be added to further improve the capacity retention rate of button batteries made of sodium ion double-layer solid electrolytes; compared with Comparative Examples 4-5, Example 5 of the present invention shows that cross-linked polyetherimide and poly(hexylene adipate) need to be used together, and the use of any one of them alone has no obvious effect on improving the capacity retention rate of button batteries made of sodium ion double-layer solid electrolytes.

[0089] Experimental Example 6: The solid electrolytes prepared in Example 1 and Comparative Examples 1-3 were made into button batteries, and the specific capacity under different voltage conditions was measured, and the reversible capacity was measured at 2.0-4.0V. The solid electrolytes included the sodium ion double-layer solid electrolytes prepared in Example 1 and Comparative Example 3 and the sodium ion single-layer solid electrolytes prepared in Comparative Examples 1-2. The results are shown in FIG. Figure 5 As shown, the button cell made of the sodium ion double-layer solid electrolyte prepared in Example 1 has a higher specific capacity under different voltage conditions, indicating that the sodium ion double-layer solid electrolyte has an improved specific capacity compared with the sodium ion single-layer solid electrolyte, and the effect of spin coating is better than direct casting.

[0090] Experimental Example 7: The solid electrolytes prepared in Example 1 and Comparative Examples 1-3 were made into button batteries, and the cycle performance was measured. The solid electrolytes included the sodium ion double-layer solid electrolytes prepared in Example 1 and Comparative Example 3 and the sodium ion single-layer solid electrolytes prepared in Comparative Examples 1-2. The results are shown in FIG. Figure 6 As shown, after 200 cycles, the button cell made of the sodium ion double-layer solid electrolyte prepared in Example 1 still has a higher discharge specific capacity than that of Comparative Examples 1-3, and the capacity retention rate is also high, indicating that the sodium ion double-layer solid electrolyte has better cycle performance than the sodium ion single-layer solid electrolyte, and the effect of spin coating is better than direct casting.

[0091] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.

[0092] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.

Claims

1. A sodium ion double-layer solid electrolyte, comprising: An organic polymer, a sodium salt and an inorganic powder; the organic polymer comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, cross-linked polyetherimide and polyhexamethylene adipate.

2. A sodium ion double-layer solid electrolyte according to claim 1, characterized in that: The sodium salt is at least one of sodium bis(trifluoromethylsulfonyl imide), sodium hexafluorophosphate and sodium perchlorate; the inorganic powder is Na3Zr2Si2PO 12 、Li7La3Zr2O 12 and Li 6.4 LqCy 1.4 Ta 0.6 O 12 At least one of .

3. A sodium ion double-layer solid electrolyte according to claim 1, characterized in that: Said The mass ratio of the amount of organic polymer used to the amount of sodium salt used is 1:0.1-1.68, and the mass ratio of the amount of inorganic powder used to the amount of sodium salt used is 1:0.382-2.

5.

4. A method for preparing a sodium ion double-layer solid electrolyte, comprising: S1: dissolving an organic polymer and a sodium salt in an organic solvent to obtain a slurry, casting the slurry, and standing the slurry to dry to obtain an organic solid electrolyte; S2: Preparation of a sodium ion double-layer solid electrolyte, dissolving an inorganic powder and a sodium salt in an organic solvent to obtain an inorganic slurry, then rotating the inorganic slurry on the organic solid electrolyte prepared in S1, and letting it stand and dry to obtain a sodium ion double-layer solid electrolyte.

5. The method for preparing a sodium ion double-layer solid electrolyte according to claim 4, characterized in that: The organic polymer comprises at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyethylene oxide, cross-linked polyetherimide and polyhexanediol adipate; the sodium salt is at least one of sodium bistrifluoromethylsulfonyl imide, sodium hexafluorophosphate and sodium perchlorate; the inorganic powder is Na3Zr2Si2PO 12 、Li7La3Zr2O 12 and Li 6.4 LqCy 1.4 Ta 0.6 O 12 The organic solvent is at least one of acetonitrile, N-methylpyrrolidone and acetone.

6. The method for preparing a sodium ion double-layer solid electrolyte according to claim 4, characterized in that: The mass ratio of the amount of the organic polymer used in S1 to the amount of the sodium salt used is 1:0.08-0.8, and the amount of the organic polymer in the organic reagent is 0.05-0.15 g / ml.

7. The method for preparing a sodium ion double-layer solid electrolyte according to claim 4, characterized in that: The mass ratio of the amount of inorganic powder used in S2 to the amount of sodium salt used is 1:0.2-0.5, and the amount of inorganic powder in the organic reagent is 0.07-0.15 g / ml.

8. The method for preparing a sodium ion double-layer solid electrolyte according to claim 4, characterized in that: In the S1, the standing temperature is 23-27° C., and the standing time is 6-15 h; the drying temperature is 45-65° C., and the drying time is 4-10 h.

9. The method for preparing a sodium ion double-layer solid electrolyte according to claim 4, characterized in that: In the step S2, the standing temperature is 23-27° C., and the standing time is 10-15 h; the drying temperature is 40-55° C., and the drying time is 4-10 h.

10. A battery comprising the sodium ion double-layer solid electrolyte according to any one of claims 1 to 3 or the sodium ion double-layer solid electrolyte prepared by the method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • A method for preparing a composite electrolyte membrane for solid-state batteries

    CN108767311B

  • Positive electrode metal salt additive capable of being used for constructing positive electrode interfacial film of solid electrolyte and application of positive electrode metal salt additive

    CN114243100A